Fatigue-related changes of muscle coordination during a maximal 100-m butterfly stroke swimming: a case study - Yamakawa, K. K.; Nishiwaki, R.; Sengoku, Y. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study investigated the fatigue-related changes in muscle coordination during a maximal 100-m butterfly stroke swimming in an international level male swimmer. Four muscle synergies were extracted from the electromyography (EMG) data during the butterfly stroke in 1st-3rd laps, while five muscle synergies were extracted from the data in 4th lap. The muscle combinations and activation times in the synergy #1, #2, #3 and #4 were similar between each lap. The synergy #5 in 4th lap had a high contribution from the trapezius and rectus femoris muscles and was active in the catch phase. These results suggest that the muscle synergies during a maximal 100-m butterfly stroke swimming are not largely altered between each lap in this swimmer, although the additional neural control appeared to be related to fatigue.